International Monetary Fund Annual Report 1973. (Annual Report of the Executive Board; Annual Report of the Executive Board ;, 1973)
This paper reviews key findings of the IMF's Annual Report for the fiscal year ended April 30, 1973. The report highlights that world economic developments in 1972 and the first half of 1973 were dominated by a strong cyclical upsurge in activity, high rates of price inflation, and currency crises and unrest punctuated by another realignment of major currencies in February-March 1973. With key elements of the Bretton Woods system no longer observed, the work of reforming the international monetary system continued in the IMF through the Committee of Twenty.